Setaria cervi (Filarioidea, Onchocercidae) undressing in ungulates: altered morphology of developmental stages, their molecular detection and complete sequence cox1 gene - Lanková, Sylva; Vejl, Pavel; Melounová, Martina; Čílová, Daniela; Vadlejch, Jaroslav; Miklisová, Dana; Jankovská, Ivana; Langrová, Iva (Parasitology, 2021)
This work introduces new morphological and molecular information on the filaroid nematode Setaria cervi (Rudolphi, 1819) obtained from 13 infected game ungulates out of 96 dissected. The hosts comprised the following: a single moose (Alces alces), ten red deer (Cervus elaphus) and two sika deer (Cervus nippon) originating from the western and northern regions of the Czech Republic. Based on the complete sequences of the gene encoding mitochondrial cytochrome c oxidase subunit 1 (cox1), all 20 females and four males belonged to the species S. cervi. We detected three developmental female stages (adult fertile females, juvenile L5 females and L4 female larvae) differing in size and some morphological traits as the subtle structure of peribuccal crown and shape and features of tail knob. Such differences were described in detail for the first time. The phylogenetic relationships within the family Onchocercidae have been evaluated using new information on the cox1 sequence of S. cervi (maximum likelihood method, GTR + I + G model). In accordance with the latest phylogenetic studies, the present analysis confirmed the ancient separation of the subclass Setariinae from the remaining two onchocercid lineages Dirofilariinae and Onchocerinae.
Keywords: Setaria (Nematoda); Animals; Female; Helminth Proteins; setariáza; ženské pohlaví; Game ruminants; Setaria Nematode; Deer; setariinae; nematode; Male; Setariasis; morphology; Czech Republic; phylogenetic analysis; Česká republika; proteiny červů; Larva; zvířata; mužské pohlaví; Setaria cervi larval stages; vysoká zvěř; larva